Corporate Risk Management Disclosure And Corporate Sustainability Of Malaysia Annual Reports - Lee, Tian Koon (2014)
This main purpose of this research study is to examine the relationship of between corporate risk management disclosure and corporate sustainability. The corporate risk management consists of six types of risk such as financial risk, operations risk, empowerment risk, information processing and technology risk, integrity risk, and strategic risk. The corporate sustainability consists of economic, environmental and social. This research also tests the moderating effect of level of diversification on the relationship between corporate risk management disclosure and corporate sustainability. In this quantitative study, a total of 80 Malaysian Main Board companies' annual reports of year 2012 were selected using simple random method. All 80 annual reports were downloaded from Bursa Malaysia's official website. A content analysis method, statistical analysis and hierarchical regression analysis are used in this study. Evidence from the test results indicated that there is positive significant relationship between corporate risk management disclosure and corporate sustainability. Furthermore, the level of diversification is also found to be positively related as moderating effect between corporate risk management disclosure and corporate sustainability. Thus, it is hope that through this study can be useful to promote the transparency and improve disclosure level of the corporate risk management in Malaysian annual reports.